Novel pyrazolo[3,4-d]pyrimidines: design, synthesis, anticancer activity, dual EGFR/ErbB2 receptor tyrosine kinases inhibitory activity, effects on cell cycle profile and caspase-3-mediated apoptosis - Mai Maher; Asmaa E. Kassab; Ashraf F. Zaher; Zeinab Mahmoud (Taylor & Francis Group, 2019)
A series of novel pyrazolo[3,4-d]pyrimidines was synthesised. Twelve synthesised compounds were evaluated for their anticancer activity against 60 human tumour cell lines by NCI (USA). Compound 7d proved prominent anticancer activity. It showed 1.6-fold more potent anti-proliferative activity against OVCAR-4 cell line with IC50 = 1.74 μM. It also exhibited promising potent anticancer activity against ACHN cell line with IC50 value 5.53 μM, representing 2.2-fold more potency than Erlotinib. Regarding NCI-H460 cell line, compound 7d (IC50 = 4.44 μM) was 1.9-fold more potent than Erlotinib. It inhibited EGFR and ErbB2 kinases at sub-micromolar level (IC50 = 0.18 and 0.25 µM, respectively). Dual inhibition of EGFR and ErbB2 caused induction of apoptosis which was confirmed by a significant increase in the level of active caspase-3 (11-fold). It showed accumulation of cells in pre-G1 phase and cell cycle arrest at G2/M phase.